1998
DOI: 10.1021/bi973086q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Enzymatic Formation of 4-(β-d-Ribofuranosyl)aminobenzene 5‘-Phosphate during the Biosynthesis of Methanopterin

Abstract: A central step in the biosynthesis of the modified folate methanopterin is the condensation of p-aminobenzoic acid (pAB) and 5-phospho-alpha-D-ribosyl-1-pyrophosphate (PRPP) which produce 4-(beta-D-ribofuranosyl)aminobenzene 5'-phosphate (beta-RFA-P) [White, R. H. (1996) Biochemistry 35, 3447-3456]. This reaction, catalyzed by the enzyme beta-RFA-P synthase, is unique among known phosphoribosyltransferases in that a decarboxylation of one of the substrates (pAB) occurs during the reaction and a C-riboside rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 32 publications
4
58
2
Order By: Relevance
“…What would stabilize this negative charge on a carbon that already contains a negatively charged carboxyl group? It was suggested that ␤-RFA-P synthase contains PLP, which is known to stabilize similar intermediates during decarboxylation or deamination of amino acids, and the partially purified enzyme appeared to contain a chromophore with properties similar to those of PLP (3). However, we show here that ␤-RFA-P synthase lacks PLP and apparently any other cofactor that would be capable of stabilizing negative charge developing during the reaction.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…What would stabilize this negative charge on a carbon that already contains a negatively charged carboxyl group? It was suggested that ␤-RFA-P synthase contains PLP, which is known to stabilize similar intermediates during decarboxylation or deamination of amino acids, and the partially purified enzyme appeared to contain a chromophore with properties similar to those of PLP (3). However, we show here that ␤-RFA-P synthase lacks PLP and apparently any other cofactor that would be capable of stabilizing negative charge developing during the reaction.…”
contrasting
confidence: 54%
“…Furthermore, ␤-RFAP synthase is inhibited by pyridoxol phosphate, an analog of PLP (3), and nonenzymatic decarboxylation of pABA by PLP has been observed (16). However, ␤-RFAP synthase is not inhibited by cysteine or by several carbonyl reactive reagents known to inactivate PLP-dependent enzymes (3). In addition, the partially purified ␤-RFAP synthase from A. fulgidus showed no UV-visible absorbance at wavelengths characteristic of pyridoxal phosphate and a consensus pyridoxal phosphate-binding motif was not found in the amino acid sequence of ␤-RFAP synthase.…”
Section: Results Of Product Inhibition Studies As Compared With Pattementioning
confidence: 99%
See 1 more Smart Citation
“…12A, compound m). The enzyme catalyzing this reaction has affinity for both 4-hydroxy-and 4-aminobenzoate (304,305). In vitro and in vivo analyses used 4-aminobenzoate to elucidate the metabolic pathway.…”
Section: Reactions At the Anomeric Carbon Of Prppmentioning
confidence: 99%
“…Some kinetic constants were determined; the apparent K m 4-aminobenzoate was 58 M and the apparent K m PRPP was 3.6 mM. Pyridoxal phosphate is suggested to be involved in the reaction, but data are inconclusive in this respect, and it has been suggested that pyridoxal phosphate may be involved in the reaction in a way that does not require the carbonyl of pyridoxal phosphate (301,305).…”
Section: Reactions At the Anomeric Carbon Of Prppmentioning
confidence: 99%